The cross-linguistic influence of Arabic on the English passive voice - Lghzeel, Fatma Ali Mohamed; Noor Raha, Mohd Radzuan (Birlesik Dunya Yenilik Arastirma ve Yayincilik Merkezi, 2020)
It is difficult to describe cross-linguistic influence; however, it has been a contentious phenomenon for a long time. Whenever the speaker of a language becomes bilingual, the first language will subtly affect the new one, even if it is not used much. This is how first language influence begins since the majority of Arab English as a foreign language (EFL) learners suffer from this problem. This current research aims to study the negative influence of the native language (Arabic) on utilising the English passive voice. In this article, we aim to discover the levels of Arab EFL learners’ knowledge of the passive voice, as well as to examine the percentage of interlingual and intralingual errors. This study applies a quantitative method. Forty-six participants, who are Arab EFL learners studying at the Universiti Malaysia Pahang, engaged in the task of answering a grammar test. To conclude, the results show that Arab students have a high rate of L1 transfer on the English passive voice, and their levels of knowledge of passive voice are identified. The researchers recommend mixed methods for further research in order to provide a wider understanding about this issue.